2018
DOI: 10.3390/nu10101538
|View full text |Cite
|
Sign up to set email alerts
|

Non-Pharmacological Interventions to Reduce Unhealthy Eating and Risky Drinking in Young Adults Aged 18–25 Years: A Systematic Review and Meta-Analysis

Abstract: Alcohol use peaks in early adulthood and can contribute both directly and indirectly to unhealthy weight gain. This review aimed to systematically evaluate the effectiveness of preventative targeted interventions focused on reducing unhealthy eating behavior and linked alcohol use in 18–25-year-olds. Twelve electronic databases were searched from inception to June 2018 for trials or experimental studies, of any duration or follow-up. Eight studies (seven with student populations) met the inclusion criteria. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…School-based multicomponent educational programs that support and promote health behavior change in adolescents through interventions focused on nutrition, physical activity, stress reduction, and other healthy behaviors have shown limited sustainability and effectiveness. 8,[12][13][14] Furthermore, we did not find any studies involving rural adolescents in the United States. Adolescence is the peak time for the development of psychopathology as well.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…School-based multicomponent educational programs that support and promote health behavior change in adolescents through interventions focused on nutrition, physical activity, stress reduction, and other healthy behaviors have shown limited sustainability and effectiveness. 8,[12][13][14] Furthermore, we did not find any studies involving rural adolescents in the United States. Adolescence is the peak time for the development of psychopathology as well.…”
mentioning
confidence: 78%
“…However, school health education programs have rarely focused specifically on diabetes knowledge and prevention. School-based multicomponent educational programs that support and promote health behavior change in adolescents through interventions focused on nutrition, physical activity, stress reduction, and other healthy behaviors have shown limited sustainability and effectiveness 8,12–14. Furthermore, we did not find any studies involving rural adolescents in the United States.…”
mentioning
confidence: 80%
“…The relationship of age and health-state utilities was bell-shaped in the UK TTO EQ-5D valuation study [ 25 ] and we found increased acceptability of health problems in the 18–34-year-old age group. Perceived severity of health outcomes may play a role in the prevention of health-risk behaviours [ 26 ], an important health concern among young adults [ 27 ]. Acceptability of health problems may be linked to the perception of health risks by younger adults, although this hypothesis needs empirical testing.…”
Section: Discussionmentioning
confidence: 99%